Governance Bottlenecks in Civil Servant Pension Decree Services: A Process-Level Analysis Based on Good Corporate Governance - Eka Mayasari; Baiq El Badriati; Ummu Rosyidah (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
The issuance of civil servant pension decrees constitutes a critical public administrative service that directly affects legal certainty and financial continuity for retirees. Although formal regulations and standard operating procedures are in place, pension services frequently experience delays and uncertainty, indicating persistent governance challenges at the operational level. This study examines governance bottlenecks in the process of issuing civil servant pension decrees by applying Good Corporate Governance principles as a process-level analytical framework. This research adopts a qualitative case study approach. Data were collected through semi-structured interviews with key service actors and service users, non-participant observations of administrative processes, and analysis of relevant regulatory and administrative documents. The data were analyzed thematically using five Good Corporate Governance principles, namely transparency, accountability, responsibility, independence, and fairness, to identify governance weaknesses across service stages. Data triangulation and audit trails were applied to enhance the trustworthiness of the findings. The findings indicate that Good Corporate Governance principles are implemented primarily at a normative and procedural level, while their operational effectiveness remains uneven across the service process. Transparency is largely confined to initial procedural information, with limited visibility of service progress due to the absence of an integrated tracking mechanism. Accountability is formally defined through roles and responsibilities, but lacks systematic documentation of process performance. Procedural responsibility contributes to administrative bottlenecks, particularly during document verification and final authorization. In addition, reliance on individual authority at critical stages constrains institutional independence, while equal procedural treatment does not consistently ensure equal access to service information. This study contributes to the public governance literature by demonstrating how Good Corporate Governance principles can be applied to identify governance bottlenecks at the micro-process level of administrative services. From a practical perspective, the findings underscore the importance of process-oriented governance reforms to strengthen transparency, accountability, and institutional resilience in the delivery of civil servant pension services.